Multi degree-of-freedom position sensing by combination of laser speckle correlation and range-resolved interferometry - Charrett, Thomas O. H.; Kissinger, Thomas; Tatam, Ralph P. (SPIE - International Society for Optics and Photonics, 2019)
This paper reports on the development of an end-effector mounted, multi degree-of-freedom positioning sensor capable of measuring the (x,y,z) movements relative to an object. The instrument termed wPOS (workpiece Positioning Sensor), combines two complimentary non-contact optical techniques; laser speckle correlation (LSC) and Range-Resolved Interferometry (RRI). Laser speckle correlation is used to measure the in-plane position (x,y) relative to a reference point, while the RRI system provides an out-of-plane (z) absolute range measurement and correction of the in-plane LSC measurement for varying working distance. The concept and operating principles of the instrument is described along with details of the prototype sensor implementation and exemplar results showing accuracies of <30µm after 0.75m lateral travel and repeatability between measurements of ~7 µm
Keywords: Laser speckle; Interferometry; Range Resolved Interferometry; Displacement sensing; Positioning; Tool path; Tool speed